Loneliness in the Elderly: A Community-Based Assessment of Prevalence and Demographic Correlates in Bekasi, Indonesia - Prima, Ashar; Rahayu, Istiana; Andas, Amzal Mortin; Firman Irwanto, Moh; Lanahdiana, Lu’lu; Shoaliha, Maratun; Romantika, I Wayan (PT. Nursing Genius Care, 2026)
Background: Loneliness among the elderly is a critical public health concern associated with adverse mental and physical health outcomes. In Indonesia, rapid urbanization and shifting family structures may exacerbate this issue, yet data on its prevalence at the primary healthcare level remain limited. Objective: This study aimed to assess the prevalence of loneliness and identify key demographic correlates among community-dwelling elderly in the working area. Methods: A community-based cross-sectional study was conducted from March to June 2024. Using consecutive sampling, 109 elderly participants aged ≥60 years were enrolled. Data were collected using the validated Indonesian version of the UCLA Loneliness Scale (Version 3) and a structured demographic questionnaire. Descriptive statistics and frequency distributions were used for data analysis. Results: The study revealed that 74.3% of participants experienced mild loneliness, while 16.5% reported no loneliness, 8.3% had moderate loneliness, and 0.9% experienced severe loneliness. Significant demographic correlates included female gender (72.5%), age 60-69 years (78.9%), elementary education level (47.7%), unemployment status (69.7%), widowhood (51.4%), and low income (<IDR 1,500,000; 87.2%).Conclusion: Mild loneliness is prevalent among the elderly in this community, with distinct demographic correlates. These findings emphasize the need for targeted, community-based psychosocial interventions integrated into primary healthcare services to address loneliness among vulnerable elderly populations.